Pengaruh Senam Lansia terhadap Tingkat Stres di Puskesmas Mekarsari Desa Citeras Kecamatan Rangkasbitung Kabupaten Lebak Tahun 2023 - Wiwit Desi Intarti; Rosana Supriadi; Renince Siregar (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2024)
The elderly are those who have reached the age of 60 years and above. As they age, they often face challenges that make it difficult to accept reality, thus affecting their physiological and psychological conditions. Many elderly people experience stress, which then has an impact on the increase in physical and psychological complaints in response to the stress. Elderly gymnastics can be an effective mechanism to improve the stress-related welfare experienced by the elderly. However, the participation of the elderly in this gymnastics activity is still relatively low. The purpose of the study is to find out the “Effect of Elderly Gymnastics on Stress Levels at the Mekarsari Health Center in Citeras Village, Rangkasbitung District, Lebak Regency